Representation of Women in Politics (Study of Dumai City Legislative Elections for the 2019-2024 Period) - Ramlan Darmansyah; Ade Sartika (Institut Pendidikan Indonesia, 2021)
The research is motivated by problems related to women's interests which require women's representation in legislative institutions and influence the provisions in Law Number 8 of 2012 concerning the General Election of Members of the DPR, DPD and DPRD related to the 30% quota for women's representation. The formulation of the problem in this research is what is the form of legal guarantee for women's representation in the political realm? Then secondly, what is the level of vote acquisition for PPP female legislative candidates for the 2019-2024 election period in Dumai City? The aim of this research is to see the certainty of legal guarantees for women's representation in the political realm and to see the level of vote acquisition of female PPP party legislative candidates in the 2019-2024 elections in Dumai City. The focus of this research is to examine the results of women's votes in politics, especially in the Dumai City United Development Party (PPP) for the 2019-2024 period. This research is research that uses the library study method, where the data used comes from materials in the form of books, journals and libraries research results from various references. The results of this research show that the vote share of women from the United Development Party (PPP) in Dumai City has decreased quite significantly. The reason is, not a single female legislative candidate has succeeded in occupying a legislative seat as a female representative in the political arena.